2005
DOI: 10.1029/2005gc000988
|View full text |Cite
|
Sign up to set email alerts
|

Observations of infragravity waves at the Monterey ocean bottom broadband station (MOBB)

Abstract: [1] Infragravity waves can be observed at the 1000 m deep ocean bottom broadband seismic station MOBB on stormy as well as quiet days. When compared to the energy of the short-period ocean waves recorded at the local buoys, infragravity waves in the longer than 20 s period band are found to be mainly locally generated from shorter-period waves. Two types of modulation of the infragravity signal are observed. First, the entire infragravity band signal is modulated in-phase with tides, possibly as a result of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 27 publications
7
56
0
Order By: Relevance
“…2 are not representative of the long term condition of the seafloor. Nonetheless, as in other reports (e.g., Collins et al 2001;Dolenc et al 2005), the quiet-day snapshot is provided to show end-member scenarios that can be compared with the reference data on land. A sensor that rests on the surface of the sediment is not well coupled to the ground and is subject to tilt by bottom currents which increase the low-frequency noise levels on the horizontal components much more significantly than on the vertical component (e.g., Collins et al 2001).…”
Section: Noise Levelsmentioning
confidence: 99%
“…2 are not representative of the long term condition of the seafloor. Nonetheless, as in other reports (e.g., Collins et al 2001;Dolenc et al 2005), the quiet-day snapshot is provided to show end-member scenarios that can be compared with the reference data on land. A sensor that rests on the surface of the sediment is not well coupled to the ground and is subject to tilt by bottom currents which increase the low-frequency noise levels on the horizontal components much more significantly than on the vertical component (e.g., Collins et al 2001).…”
Section: Noise Levelsmentioning
confidence: 99%
“…IG waves also are considered to excite the Earth's hum Romanowicz 2004, 2006;Tanimoto 2005;Nishida et al 2008;Fukao et al 2010;Nishida 2013). Dolenc et al (2005) compared the power spectra of ocean-bottom seismic records at a station located offshore of the Monterey Bay in California with the wave spectral densities measured by the nearby National Oceanic and Atmospheric Administration (NOAA) buoy. They observed two types of IG wave modulations with short (30-to 40-s) and long (10-day) periods, the latter being correlated with the ocean tides at the station.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigations have shown that infragravity waves are important to sediment transport near the shoreline [Holman and Bowen, 1982;Bauer and Greenwood, 1990], currents in the surfzone [Sasaki et al, 1976;Kobayashi and Karjadi, 1996], oscillations in harbors [Okihiro et al, 1993], and fluctuations in seismic records observed on the continental shelf [Dolenc et al, 2005;Webb, 2007].…”
Section: Introductionmentioning
confidence: 99%